(untitled) (The Review of Diabetic Studies, 2025)
The rapid integration of Artificial Intelligence (AI) into organizational processes is profoundly reshaping conventional leadership models, particularly within the realm of workforce development. As Indian organizations face digital disruption and evolving workforce demands, leaders are leveraging AI technologies for informed decision-making and cultural alignment. AI can streamline internal HR processes like feedback collection, query handling, workforce planning, and performance tracking each contributing to stronger employee engagement and organizational effectiveness. This study investigates the transformative role of AI-driven leadership practices in enhancing employee engagement, digital readiness, and the cultivation of an organizational learning culture in Indian workplaces. As businesses navigate the evolving digital economy, understanding how AI influences leadership and human capital strategies becomes essential for achieving sustainable growth and competitive advantage. The research employs an exploratory and descriptive design, utilizing both quantitative and qualitative methodologies to gain a comprehensive understanding of the subject. A structured questionnaire was administered to 300 managers, HR professionals, team leaders and employees representing diverse sectors across India to gain deeper insights into organizational practices. Quantitative data were analysed using multiple regression analysis and ANOVA. The findings reveal that AI-integrated leadership significantly enhances employee engagement, fosters a digital learning culture, and improves workforce development. AI tools enhance transformational leadership qualities by facilitating data-driven decision-making and individualized training. The association between organizational learning and AI-based leadership is moderated by digital readiness. Respondents from a variety of industries noted increases in creativity, productivity, and adaptability, underscoring AI’s function as a key facilitator of worker transformation. Overall, the study indicates that AI serves as a strategic enabler of organizational performance, human resource development, and leadership transformation in addition to being a technological advancement. These insights carry practical implications for policymakers, business leaders, and HR professionals striving to leverage AI for inclusive and forward-looking workforce strategies. The research highlights the importance of investing in digital infrastructure, leadership training, and change management to maximize the potential of AI in shaping resilient and agile organizations in India’s rapidly changing business environment.